Teledentistry - Kumar, Sajeesh (Health Informatics, 2015)
This book provides a comprehensive review of the importance of communication and digital technology in dentistry. The exciting and rapidly developing field of teledentistry has evolved considerably as the techniques have improved; these encompass high-resolution digital imaging, image storage and transmission to expert disease monitoring centers, image compression, data security and intelligent systems, each of which have opened new vistas in patient care, distance learning for dental personnel and dental care education for patients. Teledentistry is a means of achieving equity in specialist dental service delivery with acceptable levels of care that is evidence based, even in situations where trained specialists personnel and infrastructure resources are limited. This multiauthored sourcebook encapsulates global efforts in the development of teledentistry with contributions from many international experts with first- hand experience. They not only describe what is already available but also postulate what the future holds for teledentistry. Teledentistry presents a concise and yet thorough review of the subject to anyone, independent of their knowledge of the technology. It is designed to be used by all, including dentists, nurses, allied health professionals and students.